A Novel Development of TRIZ-Analogic Construction Interface Problem Identification and Solutions Framework - Sou-Sen Leu; Chih-Yu Yang; Yao-Jen Hsu (Advances in Civil Engineering)
One of the critical factors of project success is the interface management. Past project interface management mainly relies on knowledge and experience of the project managers. The existing studies of project interface management also mainly focused on the definition and the classification of project interfaces. There is no workable and flexible framework for construction interface problem identification and solutions. This study conducted an analogic study of contradiction matrix at Theory of Inventive Problem Solving (TRIZ) to develop such a framework. This research collected around six hundred interface management cases from civil works and building projects. For comparison, this research defined an experimental group (TRIZ case) and a control group (experience-oriented solution case) based on the concept of clinical experiments in medical science to evaluate and improve the rationality of the matrix. Subsequently, based upon the theory of information retrieval (IR), this research conducted statistical evaluation and TRIZ features remedies to develop generalized construction interface problem identification and solutions. For solving project management interface problems, the TRIZ-analogic construction interface problem identification and solutions framework provides a systematic approach to develop more robust solutions for interface problems in construction engineering rather than just simply relying on intuitive experience.